The production and secretion of tRNA-derived RNA fragments in the corn smut fungus Ustilago maydis - Yoshimoto, Rei; Ishida, Fumiko; Yamaguchi, Miyuki; Tanaka, Shigeyuki (Frontiers in Fungal Biology, 2022)
The biogenesis of small non-coding RNAs is a molecular event that contributes to cellular functions. The basidiomycete fungus Ustilago maydis is a biotrophic pathogen parasitizing maize. A hallmark of its genome structure is an absence of RNAi machinery including Dicer and Argonaute proteins, which are responsible for the production of small RNAs in other organisms. However, it remains unclear whether U. maydis produces small RNAs during fungal growth. Here we found that U. maydis cells accumulate approximately 20-30 nucleotides of small RNA fragments during growth in the axenic culture condition. The RNA-seq analysis of these fragments identified that these small RNAs are originated from tRNAs and 5.8S ribosomal RNA. Interestingly, majority of their sequences are generated from tRNAs responsible for asparagine, glutamine and glycine, suggesting a bias of origin. The cleavage of tRNAs mainly occurs at the position near anticodon-stem-loop. We generated the deletion mutants of two genes nuc1 and nuc2 encoding RNase T2, which is a candidate enzyme that cleaves tRNAs. The deletion mutants of two genes largely fail to accumulate tRNA-derived RNA fragments. Nuc1 and tRNA are co-localized at the tip of budding cells and tRNA fragment could be detected in culture supernatant. Our results suggest that specific tRNAs would be cleaved during secretory processes and tRNA fragments might have extracellular functions.